2014
DOI: 10.1186/1880-6805-33-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between the melanopsin gene polymorphism OPN4*Ile394Thr and sleep/wake timing in Japanese university students

Abstract: BackgroundIn our previous studies, we found that the Ile394Thr SNP in the melanopsin gene (OPN4) was functionally associated with the pupillary light reflex. This indicates the possibility that OPN4*Ile394Thr is associated with other non-image forming responses. The aim of this study was therefore to determine whether OPN4*Ile394Thr is associated with sleep/wake timing.MethodsA total of 348 healthy Japanese university students participated in this study. Scalp hair was used to genotype the Ile394Thr SNP of OPN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…One possible explanation to this phenomenon of normal sleep quality despite reduced melanopsin activity was proposed as the absence of the TT allele of the melanopsin gene (OPN4) (Adhikari et al 2016b). The TT genotype has been shown to be less sensitive to light and associated with disturbed sleep quality (Roecklein et al 2012;Higuchi et al 2013;Lee et al 2013Lee et al , 2014. The role of the TT genotype cannot be ruled out in our study.…”
Section: Discussionmentioning
confidence: 63%
“…One possible explanation to this phenomenon of normal sleep quality despite reduced melanopsin activity was proposed as the absence of the TT allele of the melanopsin gene (OPN4) (Adhikari et al 2016b). The TT genotype has been shown to be less sensitive to light and associated with disturbed sleep quality (Roecklein et al 2012;Higuchi et al 2013;Lee et al 2013Lee et al , 2014. The role of the TT genotype cannot be ruled out in our study.…”
Section: Discussionmentioning
confidence: 63%
“… 80 Lee et al demonstrated that the rs1079610 SNP in OPN4 , previously functionally associated with pupillary light reflex and light sensitivity, 81 was associated with habitual sleep timing in Japanese university students. 82 While students of all three genotypes of this SNP had relatively low MEQ scores, those who were homozygous CC had significantly later bedtimes and midpoints of sleep. 82 …”
Section: Chronotypementioning
confidence: 91%
“… 82 While students of all three genotypes of this SNP had relatively low MEQ scores, those who were homozygous CC had significantly later bedtimes and midpoints of sleep. 82 …”
Section: Chronotypementioning
confidence: 91%
“…Next, circadian photoentrainment of hOPN4 AAV-treated Opn4 − / − Cre +/+ mice was examined. It has previously been suggested these behaviours may be disrupted in individuals with either Pro10Leu or Thr394Ile ( 9 , 13 ). To test this association, a circadian screen was conducted using passive infra-red (PIR) detection to monitor the locomotor activity of Opn4 − / − Cre +/+ mice injected with hOPN4 WT , Pro10Leu and Thr394Ile AAV.…”
Section: Resultsmentioning
confidence: 99%
“…These pupil deficits were not seen in individuals with the CT and CC genotypes. Lee et al ( 13 ) also found that individuals with the Thr394Ile CC genotype had disrupted sleep-wake timing, compared to CT or TT genotypes.…”
Section: Introductionmentioning
confidence: 96%